Normative Analysis of Assistance Mechanisms as Legal Instruments in the Development of Community-Based Tourism Villages in Central Magelang District - Swasti Gama Bhakti, Indira; RM. Mahendradi (Jurnal Hukum In Concreto, 2025)
The objective of this study is to analyze the effectiveness of mentoring in promoting community-based tourism village development in Magelang Tengah District, Magelang City. The impetus for this study is twofold: first, to examine the untapped potential of local resources as tourism assets, and second, to explore the significance of community empowerment in the sustainable management of these resources. The research was conducted using a qualitative approach, which included participatory observation, focus group discussions (FGDs), and the distribution of evaluative questionnaires to residents in Panjang and Kemirirejo villages. The findings indicate that academic mentoring contributes to improving community understanding of the concept of tourism villages, the formation of tourism-aware groups, and the emergence of local initiatives in revitalizing public spaces based on local culture. Nevertheless, the development of tourism villages remains contingent on interdisciplinary collaboration, particularly from local governments and businesses. The study's findings suggest the integration of mentoring programs into regional development planning (Musrenbang) and the enhancement of community capacity through sustainable training.